Dolcetto o carretto? Alcune questioni di carattere esegetico tra Anthesteria e Diasia - Giuman, Marco (O T I V M, 2024)
In Aristophanes’ Clouds (lines 855-864) the protagonist of the play, Strepsiades, remembers to have given his son Phidippides, still a child, "a little cart" (hamaxis) during the Diasia festival. Aristophanes' testimony seems to contradict a significant volume of information, primarily of iconographic character, which seems to associate the gift of carts not with the Diasia festival but with the Anthesteria. Reviewing literary and iconographic sources with a comparative approach, this contribution demonstrates that the hamaxis mentioned by Aristophanes cannot be understood as the wheeled toy cart received as a gift and used by children during the Anthesteria, but rather as a miniature model if not as a candy.